Fog Computing Architecture in higher education institutions - Sawsan Ali Hamid (Genius Journals, 2023)
The internet of things (IoT) and cloud computing are two contemporary innovations that have altered academics and business as well as influenced our daily lives in many ways. By moving processing to network edge nodes like mobile collaborative devices or stationary nodes with integrated data storage, computing, and communication devices, fog computing expands the capabilities of cloud computing. The researcher in this study suggested an architecture model for higher education institutions.
Keywords: Fog computing; Fog computinglatency; higher education